Enhancement Effects of Co Doping on Interfacial Properties of Sn Electrode-Collector: A First-Principles Study - Zhang, P.; Wang, Y.; Lei, W.; Zou, Y.; Jiang, W.; Ma, Z.; Lu, Chunsheng (AMER CHEMICAL SOC, 2019)
The Co doping effects on the interfacial strength of Sn electrode-collector interface for lithium-ion batteries are investigated by using first-principles calculations. The results demonstrate that by forming strong chemical bonds with interfacial Sn, Li, and Cu atoms, Co doping in the interface region can enhance interfacial strengths and stabilities during lithiation. With doping, the highest strengths of Sn/Cu (1.74 J m-2) and LiSn/Cu (1.73 J m-2) interfaces are 9.4 and 17.7% higher than those of the corresponding interface systems before doping. Besides, Co doping can reduce interface charge accumulation and offset the decreasing interfacial strength during lithiation. Furthermore, the interfacial strength and electronic stability increase with rising Co content, whereas the increasing formation heat may result in thermodynamic instability. On the basis of the change of formation heat with Co content, an optimal Co doping content has been provided.